Myasthenia Gravis: From the Viewpoint of Pathogenicity Focusing on Acetylcholine Receptor Clustering, Trans-Synaptic Homeostasis and Synaptic Stability - Takamori, Masaharu (Frontiers in Molecular Neuroscience, 2020)
Myasthenia gravis (MG) is a disease of the postsynaptic neuromuscular junction (NMJ) where nicotinic acetylcholine (ACh) receptors (AChRs) are targeted by autoantibodies. Search for other pathogenic antigens has detected the antibodies against muscle-specific tyrosine kinase (MuSK) and low-density lipoprotein-related protein 4 (Lrp4), both causing pre- and post-synaptic impairments. Agrin is also suspected as a fourth pathogen. In a complex NMJ organization centering on MuSK: (1) the Wnt non-canonical pathway through the Wnt-Lrp4-MuSK cysteine-rich domain (CRD)-Dishevelled (Dvl, scaffold protein) signaling acts to form AChR prepatterning with axonal guidance; (2) the neural agrin-Lrp4-MuSK (Ig1/2 domains) signaling acts to form rapsyn-anchored AChR clusters at the innervated stage of muscle; (3) adaptor protein Dok-7 acts on MuSK activation for AChR clustering from “inside” and also on cytoskeleton to stabilize AChR clusters by the downstream effector Sorbs1/2; (4) the trans-synaptic retrograde signaling contributes to the presynaptic organization via: (i) Wnt-MuSK CRD-Dvl-β catenin-Slit 2 pathway; (ii) Lrp4; and (iii) laminins. The presynaptic Ca2+ homeostasis conditioning ACh release is modified by autoreceptors such as M1-type muscarinic AChR and A2A adenosine receptors. The post-synaptic structure is stabilized by: (i) laminin-network including the muscle-derived agrin; (ii) the extracellular matrix proteins (including collagen Q/perlecan and biglycan which link to MuSK Ig1 domain and CRD); and (iii) the dystrophin-associated glycoprotein complex. The study on MuSK ectodomains (Ig1/2 domains and CRD) recognized by antibodies suggested that the MuSK antibodies were pathologically heterogeneous due to their binding to multiple functional domains. Focussing one of the matrix proteins, biglycan which functions in the manner similar to collagen Q, our antibody assay showed the negative result in MG patients. However, the synaptic stability may be impaired by antibodies against MuSK ectodomains because of the linkage of biglycan with MuSK Ig1 domain and CRD. The pathogenic diversity of MG is discussed based on NMJ signaling molecules.